2017
DOI: 10.3390/min7030041
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur Isotope Fractionation as an Indicator of Biogeochemical Processes in an AMD Passive Bioremediation System

Abstract: Sulfate, the main dissolved contaminant in acid mine drainage (AMD), is ubiquitous in watersheds affected by coal and metal mining operations worldwide. Engineered passive bioremediation systems (PBS) are low-cost technologies that remediate sulfate contamination by promoting (1) precipitation of sulfate-bearing compounds, such as schwertmannite and gypsum; and (2) microbially-mediated sulfate reduction (BSR) to sulfide with subsequent precipitation of sulfide minerals. In this study, chemical and sulfur isoto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Pyrite leaching experiments demonstrate that the quantitative conversion of pyrite to sulfate results in only minor sulfur isotope fractionation (∆ 34 S SO4-FeS2 ) under acidic, aerobic-biotic, or abiotic conditions ranging between −1.3% and +0.4% [63,[70][71][72][73][74]. In addition, processes like precipitation and dissolution of secondary sulfate phases were demonstrated to produce negligible S isotope fractionation (e.g., ∆ 34 S schwertmannite-sulfate −0.2% -+0.3% and ∆ 34 S H-jarosite-sulfate +0.3% -+1.1% ) [75][76][77]. Although these relatively small S isotope fractionation factors allow the identification of the parent sulfides in ARD-impacted water, the seasonal precipitation and dissolution cycles of sulfate minerals might cause small variations in the isotopic composition of sulfate as well.…”
Section: Sulfur Isotope Signatures Of Pyrite Leachingmentioning
confidence: 99%
See 1 more Smart Citation
“…Pyrite leaching experiments demonstrate that the quantitative conversion of pyrite to sulfate results in only minor sulfur isotope fractionation (∆ 34 S SO4-FeS2 ) under acidic, aerobic-biotic, or abiotic conditions ranging between −1.3% and +0.4% [63,[70][71][72][73][74]. In addition, processes like precipitation and dissolution of secondary sulfate phases were demonstrated to produce negligible S isotope fractionation (e.g., ∆ 34 S schwertmannite-sulfate −0.2% -+0.3% and ∆ 34 S H-jarosite-sulfate +0.3% -+1.1% ) [75][76][77]. Although these relatively small S isotope fractionation factors allow the identification of the parent sulfides in ARD-impacted water, the seasonal precipitation and dissolution cycles of sulfate minerals might cause small variations in the isotopic composition of sulfate as well.…”
Section: Sulfur Isotope Signatures Of Pyrite Leachingmentioning
confidence: 99%
“…This would help to improve our ability to evaluate the chemical evolution of both mine waste material and the impacted water systems, potentially informing ARD control measures in a timely manner. In addition to tracking ARD generation and transportation, isotopes also can be used in evaluating the effectiveness of different remediation methods, for example, passive treatment systems [75,149].…”
mentioning
confidence: 99%
“…However, since our results of the statistical calculation (details are shown below) suggested that some mines have required AMD treatment for over 150 years [13,14] and other groups suggested that more than 1000 years of treatment will be necessary [15] in the current situation, more sustainable treatment to reduce both AMD generation [16,17] and treatment cost [18] is needed. To reduce the treatment cost of the addition of chemicals and of sludge generation, for example, a passive treatment that utilizes the natural environment of mines, such as topography, plants, and microorganisms, has attracted attention as a sustainable AMD treatment based on new concepts [19][20][21]. Several researchers are trying to successfully reuse this sludge as an industrial material [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…For field purposes, these results have shown that handheld meters for DO and conductivity could serve for on-site monitoring of plant health and metal reduction, respectively. Common trends among metals were observed; from the largescale experiment, vetiver accumulated greater Fe (17,300 µg g -1 ), Al (3405 µg g -1 ), Mn (1080 µg g -1 ), Zn (113 µg g -1 ) and Cr (62.3 µg g -1 ), with lower Ni (41.2 µg g -1 ), Cu (24.6 µg g -1 ) and Pb (5.37 µg g -1 , [3][4][5] Fe, Al, and Mn. 4 Several plants have been screened for AMD tolerance, including Typha latifolia, Scirpus validus, and many others.…”
Section: Discussionmentioning
confidence: 88%
“…Effect of Vetiver grass treatment on dissolved SO 4 2-(mean±SD, n = 3 biological replicates) of the Tab-Simco AMD across planting densities (4,3,2 and no plants) over time (0, 10, 20 and 30 days). ..................................................27…”
Section: Figurementioning
confidence: 99%